The Current Crisis in Human Resources for Health in Africa - Gasim Omer Elkhalifa (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
The current crisis in human resources for health in Africa has reached a serious level in many countries. A complex set of reasons has contributed to this problem, some exogenous, such as the severe economic measures introduced by structural adjustment, which often result in cutbacks in the number of health workers while some endogenous reasons, including misdirected human resource and training policies, weak institutions, and inappropriate structures